Bioprinting of bespoke islet-specific niches to promote maturation of stem cell-derived islets - Myungji Kim; Seungyeon Cho; Dong Gyu Hwang; In Kyong Shim; Song Cheol Kim; Jiwon Jang; Jinah Jang (Nature Communications)
Abstract Pancreatic islets are densely packed cellular aggregates containing various hormonal cell types essential for blood glucose regulation. Interactions among these cells markedly affect the glucoregulatory functions of islets along with the surrounding niche and pancreatic tissue-specific geometrical organization. However, stem cell (SC)-derived islets generated in vitro often lack the three-dimensional extracellular microenvironment and peri-vasculature, which leads to the immaturity of SC-derived islets, reducing their ability to detect glucose fluctuations and insulin release. Here, we bioengineer the in vivo-like pancreatic niches by optimizing the combination of pancreatic tissue-specific extracellular matrix and basement membrane proteins and utilizing bioprinting-based geometrical guidance to recreate the spatial pattern of islet peripheries. The bioprinted islet-specific niche promotes coordinated interactions between islets and vasculature, supporting structural and functional features resembling native islets. Our strategy not only improves SC-derived islet functionality but also offers significant potential for advancing research on islet development, maturation, and diabetic disease modeling, with future implications for translational applications.